Participatory modelling of community forest landscape - Vanclay, J.K.; Prabhu, Ravi; Sinclair, Fergus L. (Univesity of Queensland, 2003)
FLORES, the Forest Land Oriented Resurce Envisioning System, is a framework to facilitate quantitative modelling of ecological, economic and social issues at the landscape scale. This special issue of journal describes the evolution of FLORES from a concept to a series of models calibrated for diverse locations, and documents lessons learned. This simulation modelling approach addresses interdisciplinary issues, where people are strongly interacting with forest resources. The idea to construct and use landscape-scale models of the frontier, based on simulating households decisions and land use at a spatial scale close to the field level.